Inflammatory Myofibroblastic Tumor of the Urinary Bladder of a Young Female: A Case Report on Diagnosis and Management Challenges - Sulaiman Almutairi (Journal of Pharmacy and Bioallied Sciences)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor with intermediate biologic potential, in which lack of understanding often poses difficulties in preoperative diagnosis and management. We report a case in which a 25-year-old female patient not known to have any medical illness presented with gross hematuria for one month. The patient was investigated with urine analysis, urine culture, urine cytology, and Ct-Urogram at a urology clinic. Her investigation showed a urinary bladder dome enhancing mass 3.6 * 3.8 * 3.3 cm with minimal surrounding perivesical stranding worrisome for early peritoneal carcinomatosis. She underwent cystoscopy and transurethral bladder tumor resection; resection was not complete due to the size of bladder mass. Six units of packed red blood cells were given. Histopathology showed IMT. Case was discussed in the tumor board and the patient underwent laparoscopic urachal resection and partial cystectomy. Discharged on day three post-op with Foley catheter and appointment for cystogram after 2 weeks. Histopathology confirms the diagnosis of IMT with four millimeters of free margin and two benign regional reactive lymph nodes. Patients were followed for two years with no sign of recurrence or any lower urinary tract symptoms. Our report reinforces the standard diagnostic and management approach, supporting consistent findings and successful surgical strategies, to enhance patient care and understanding of this rare neoplasm.